2015
DOI: 10.1242/jeb.117291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sublethal doses of glyphosate on honeybee navigation

Abstract: Glyphosate (GLY) is a herbicide that is widely used in agriculture for weed control. Although reports about the impact of GLY in snails, crustaceans and amphibians exist, few studies have investigated its sublethal effects in non-target organisms such as the honeybee Apis mellifera, the main pollen vector in commercial crops. Here, we tested whether exposure to three sublethal concentrations of GLY (2.5, 5 and 10 mg l : corresponding to 0.125, 0.250 and 0.500 μg per animal) affects the homeward flight path of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(159 citation statements)
references
References 37 publications
1
145
0
13
Order By: Relevance
“…Acute and oral contact with chlormequat is considered to be practically non-toxic to honeybees, and its LD 50 is similar to that of glyphosate, > 100 µg per bee (EPA 2007). However, it was recently shown that the sub-lethal dose of 0.5 µg of glyphosate per bee influences honeybee navigation (Balbuena et al 2015), and it is also necessary to consider that the pesticide doses we detected in the bees were presumably low because pesticides undergo metabolic changes in organisms. This phenomenon is more likely to have occurred in the dead than the dying individuals and is in line with the relatively low amount of chlormequat found in the dead bees.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Acute and oral contact with chlormequat is considered to be practically non-toxic to honeybees, and its LD 50 is similar to that of glyphosate, > 100 µg per bee (EPA 2007). However, it was recently shown that the sub-lethal dose of 0.5 µg of glyphosate per bee influences honeybee navigation (Balbuena et al 2015), and it is also necessary to consider that the pesticide doses we detected in the bees were presumably low because pesticides undergo metabolic changes in organisms. This phenomenon is more likely to have occurred in the dead than the dying individuals and is in line with the relatively low amount of chlormequat found in the dead bees.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, the main culprits are believed to be newly developed systemic insecticides, such as neonicotinoids and fipronil, that entered the market in the mid-1990s (Aliouane et al 2009;Mommaerts et al 2010;Blacquiere et al 2012); however, the pesticides affecting bees include not only insecticides but also fungicides and herbicides (Johnson et al 2010;Maini et al 2010;Pettis et al 2013). Recently, sub-lethal doses of glyphosate were reported to negatively influence honeybee navigation (Balbuena et al 2015), and in another study, chlormequat poisoning was found to resemble anticholinesterase toxicity (Nisse et al 2015). However, previous studies did not consider desiccants and plant growth regulators, such as quaternary ammonium pesticides (quats), to be contaminants of honeybee hives.…”
mentioning
confidence: 99%
“…For example, tillage and herbicides, which are commonly used to clear land, are known to disrupt existing nests (Shuler et al 2005) and potentially affect navigation for some species (Balbuena et al 2015). Whether these patterns apply broadly to most bees is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate, the most commonly reported herbicide, is used to assist in land clearing and as part of general maintenance to control invasive plant species. It has been shown to affect navigation and beta-carotene levels in honey bees (Helmer et al 2014;Balbuena et al 2015) among other effects, although this is not likely to be a long-term problem for bees in prairies due to the limited use after establishment and short persistence in soils (Syan et al 2014). However, significant concern has been raised about the persistence of other agrochemicals, particularly neonicotinoids, in the soil after a site is reconstructed (Goulson 2013).…”
Section: Land Clearing and Preparationmentioning
confidence: 99%
“…Em bioensaios de laboratório, doses recomendadas do herbicida glifosato, usado no controle de certas plantas invasoras, afetaram o comportamento das abelhas quanto à sensibilidade à sacarose (Herbert et al, 2014), a habilidade de navegação (Balbuena et al, 2015) e o estabelecimento de sistemas complexos de associação (Herbert et al, 2014). Isto pode impactar a capacidade de forrageamento, coleta de alimento e retorno para a colônia.…”
Section: O Uso De Agrotóxicos Na Agriculturaunclassified